2015
DOI: 10.1038/bmt.2015.196
|View full text |Cite
|
Sign up to set email alerts
|

Cellular engineering and therapy in combination with cord blood allografting in pediatric recipients

Abstract: Cord blood (CB) transplantation is an alternate source of human hematopoietic progenitor cells for allogeneic stem cell transplantation in children and adolescents with both malignant and nonmalignant diseases. Current limitations included delay in hematopoietic reconstitution, increased incidence of primary graft failure and slow cellular immunoreconstitution. These limitations lead to a significant increase in primary graft failure, infectious complications and increased transplant-related mortality. There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Co-transplantation of a CB unit with ex vivo expanded progenitors has shown to improve engraftment and accelerate neutrophil recovery in CB transplant (Pineault and Abu-Khader 2015;Cairo et al 2016). However, platelets recovery remains a major issue given its extended delays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-transplantation of a CB unit with ex vivo expanded progenitors has shown to improve engraftment and accelerate neutrophil recovery in CB transplant (Pineault and Abu-Khader 2015;Cairo et al 2016). However, platelets recovery remains a major issue given its extended delays.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy has been focused on the ex vivo expansion of HSPC prior to transplantation which has now been tested in several clinical trials (Pineault and Abu-Khader 2015;Norkin et al 2013;Delaney et al 2005;Cairo et al 2016;de Lima et al 2012). Indeed, decreased graft failure and accelerated neutrophil recovery have been reported in patients undergoing double CB transplantation with an expanded and unmanipulated units, each unit providing short-and long-term engraftment, respectively (de Lima et al 2012;Delaney et al 2010;Horwitz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Here, HPDSCs are perfusate from full‐term placenta with minimal manipulation. Ongoing clinical studies have demonstrated that adding HPDSCs as an adjuvant with UCBT in patients with malignant and nonmalignant diseases has had no adverse effects and may reduce the incidence of aGVHD .…”
Section: Discussionmentioning
confidence: 99%
“…Human placental‐derived stem cells (HPDSCs) are a source of stem cells obtained by Celgene Cellular Therapeutics (CCT)'s proprietary process involving perfusion of donated full‐term placentas and depletion of red blood cells, nonviable cells, and tissue debris . Although both HPDSCs and human umbilical cord blood (UCB) originate from placentas, the processing, that is, perfusion of placentas versus gravity collection of blood, has resulted in phenotypic and functional differences between these two cell products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation